2002
DOI: 10.1038/nature01107
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic view of the Plasmodium falciparum life cycle

Abstract: The completion of the Plasmodium falciparum clone 3D7 genome provides a basis on which to conduct comparative proteomics studies of this human pathogen. Here, we applied a high-throughput proteomics approach to identify new potential drug and vaccine targets and to better understand the biology of this complex protozoan parasite. We characterized four stages of the parasite life cycle (sporozoites, merozoites, trophozoites and gametocytes) by multidimensional protein identification technology. Functional profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
1,094
3
18

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,189 publications
(1,176 citation statements)
references
References 44 publications
61
1,094
3
18
Order By: Relevance
“…Interestingly, Pflpd1 and Pflpd2 transcripts and protein products are differentially expressed in P. falciparum gametocytes compared with the asexual stages, as assessed by both proteomic approaches and oligonucleotide microarrays [28,29]. The mass spectrometry data suggest that the relative abundance of PfLPD1, as crudely measured by percent sequence coverage, is ~48% for gametocytes, 21% for trophozoites, 6% for sporozoites and 3% for merozoites.…”
Section: The Gcv and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Pflpd1 and Pflpd2 transcripts and protein products are differentially expressed in P. falciparum gametocytes compared with the asexual stages, as assessed by both proteomic approaches and oligonucleotide microarrays [28,29]. The mass spectrometry data suggest that the relative abundance of PfLPD1, as crudely measured by percent sequence coverage, is ~48% for gametocytes, 21% for trophozoites, 6% for sporozoites and 3% for merozoites.…”
Section: The Gcv and Pathogenesismentioning
confidence: 99%
“…phagocytic cells) contains gcv genes whose products could guarantee the maintenance of the NAD + pool under O 2 -limiting conditions [26]. Moreover, a specific gcvB locus of Brucella abortus has been shown to be necessary for sustained infection in a model host and is presumed to be part of an unknown mechanism for long-term persistence, particularly during states of non-replication [27].Interestingly, Pflpd1 and Pflpd2 transcripts and protein products are differentially expressed in P. falciparum gametocytes compared with the asexual stages, as assessed by both proteomic approaches and oligonucleotide microarrays [28,29]. The mass spectrometry data suggest that the relative abundance of PfLPD1, as crudely measured by percent sequence coverage, is ~48% for gametocytes, 21% for trophozoites, 6% for sporozoites and 3% for merozoites.…”
mentioning
confidence: 99%
“…MAEBL was identified in P. yoelii and P. falciparum blood stage parasites as a minor membrane protein with erythrocyte binding activity expressed in the apical organelles and on the surface of invasive merozoites [3][4][5][6]. Expressed abundantly in sporozoites, MAEBL appears to be important for sporozoite invasion into the mosquito salivary glands and in establishing exoerythrocytic schizonts [6][7][8][9][10][11][12]. It has been reported that sera from infected individuals living in a malaria endemic region of western Kenya recognized M2 recombinant antigen and had the ability to inhibit M2-erythrocyte binding [6].…”
Section: Malaria; Plasmodium Falciparum; Maebl; Erythrocyte Binding Pmentioning
confidence: 99%
“…Infected erythrocytes were enriched from these samples, fractionated, and total proteome of the circulating parasites were analyzed. From this study, we have identified 88 proteins from Pf and 16 proteins from Pv and compared them with the proteome profile of ring stages of the laboratory strain 3D7 [12,14,15]. Our analysis reveals the presence of known and potential drug targets as well as proteins that are abundantly expressed in patient-derived parasites but never reported in laboratory cultures.…”
Section: Introductionmentioning
confidence: 99%